National Framework for Climate Services (NFCS) development for Guatemala and Honduras - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Public sector in Guatemala and Honduras have been advancing the National Framework for Climate Services (NFCS) formulation that aims to coordinate inter-institutional collaborations to the establishment of climate services.